Perancangan Aplikasi Monitoring dan Evaluasi Penerapan Masterplan E-Government - Afifah Nurul Izzati; Candra Adipradana; Mohammad Saichu Nidom (Syntax Literate, 2023)
E-government or SPBE aims to organize good governance and improve effective and efficient public services. In order for e-government development policies to be implemented systematically and integrated, an e-government master plan is needed. However, in the implementation of the e-government masterplan, there are still several challenges that arise that can hinder the successful implementation of the e-government masterplan. So monitoring and evaluation related to the implementation of the e-government master plan that has been made is needed so that the targets listed in the e-government master plan can be achieved. The purpose of this study is to design a monitoring and evaluation application for the implementation of the e-government master plan in Indonesia. The research was conducted using qualitative methods by collecting data through interview techniques to informants with case studies in Kediri Regency. The purpose of designing this application is to make it easier for users, namely the local government of Kediri Regency to monitor and evaluate the implementation of the e-government master plan.